Colloidal Synthesis of Quaternary Wurtzite Cu3AlSnS5 Nanocrystals and Their Photoresponsive Properties. Issue 4 (4th February 2015) - Bai, Tianyu; Xing, Shanghua; Lou, Yue; Chen, Cailing; Huang, He; Li, Chunguang; Shi, Zhan; Feng, Shouhua
Abstract Novel wurtzite Cu3AlSnS5 nanocrystals with uniform size and shape are synthesized for the first time using a facile colloidal synthetic approach. The nanocrystals are characterized in detail and have a band gap of 1.35 eV. The photoresponsive behavior indicates their potential application in solar energy conversion devices.